2019
DOI: 10.5937/scriptamed50-22426
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Benzodiazepine prescribing patterns in the primary healthcare of the Republic of Srpska

Abstract: Background: Benzodiazepines (BZDs) are very often inappropriately prescribed drugs. The aim of this study is to analyse physicians' prescribing patterns for BZD in Republic of Srpska, and to assess to what extent primary diagnosis determine the dose and the length of use of BZDs. Methods: A retrospective analysis of the physicians' prescription habits based on the database of Family Medicine Information Systems of Republic of Srpska, as well as on data from patient's medical record were performed. Patients' so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Studija sprovedena u Republici Srpskoj, koja je uključila i pacijente s mentalnim oboljenjima, pokazala je slične rezultate kao naša studija. Žene, stariji pacijenti i oni koji žive u urbanim sredinama koristili su BZD u dužem periodu 9 . U istoj studiji je, takođe, pokazano da ljudi koji žive sami češće koriste BZD, za razliku od naše studije gde su ljudi koji su u braku češće koristili BZD.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Studija sprovedena u Republici Srpskoj, koja je uključila i pacijente s mentalnim oboljenjima, pokazala je slične rezultate kao naša studija. Žene, stariji pacijenti i oni koji žive u urbanim sredinama koristili su BZD u dužem periodu 9 . U istoj studiji je, takođe, pokazano da ljudi koji žive sami češće koriste BZD, za razliku od naše studije gde su ljudi koji su u braku češće koristili BZD.…”
Section: Discussionunclassified
“…The study conducted in the Republic of Srpska, which also included patients with mental disorders, showed similar results as our study. Females, the elderly and patients living in urban areas used BZDs for longer periods 9 . The same study also showed that people who live alone use BZDs more often, unlike the results of our study where married persons used BZDs more frequently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recommendations are that in these conditions BZDs are used only in case of agitation. A study conducted in the Republic of Srpska found that as many as a quarter of BZDs were prescribed for non-psychiatric diagnoses such as musculoskeletal diseases, followed by epilepsy, hypertension, arrhythmias, and chest pain [ 5 ]. Maric et al found that, in South-Eastern Europe, as many as 81.9% of patients were discharged from psychiatric clinics with a high dose of BZDs (equivalent to 5 mg lorazepam) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%